Isolation and Electrochemical Analysis of a Facultative Anaerobic Electrogenic Strain Klebsiella sp. SQ-1 - Zhou Lei; Tang Tuoxian; Deng Dandan; Wang Yayue; Pei Dongli (Polish Journal of Microbiology, 2024)
Electricigens decompose organic matter and convert stored chemical energy into electrical energy through extracellular electron transfer. They are significant biocatalysts for microbial fuel cells with practical applications in green energy generation, effluent treatment, and bioremediation. A facultative anaerobic electrogenic strain SQ-1 is isolated from sludge in a biotechnology factory. The strain SQ-1 is a close relative of Klebsiella variicola. Multilayered biofilms form on the surface of a carbon electrode after the isolated bacteria are inoculated into a microbial fuel cell device. This strain produces high current densities of 625 μA cm–2 by using acetate as the carbon source in a three-electrode configuration. The electricity generation performance is also analyzed in a dual-chamber microbial fuel cell. It reaches a maximum power density of 560 mW m–2 when the corresponding output voltage is 0.59 V. The facultative strain SQ-1 utilizes hydrous ferric oxide as an electron acceptor to perform extracellular electricigenic respiration in anaerobic conditions. Since facultative strains possess better properties than anaerobic strains, Klebsiella sp. SQ-1 may be a promising exoelectrogenic strain for applications in microbial electrochemistry.